Sling-bridge technique: new technique in extracorporeal septorhinoplasty - Omer, Goran Latif (Frontiers in Surgery, 2024)
Extensive septal deviations requiring advanced correction beyond conventional methods. Extracorporeal rhinoplasty technique, involving complete septum removal, reshaping, and reinsertion. While this technique possesses unacceptable risks, the current study aims to introduce a new approach, the sling-bridge technique to enhance and simplify extracorporeal septorhinoplasty, with more tip control and better integrity within the keystone area.This prospective analytical study included 50 patients with crooked nasal septum who underwent extracorporeal septorhinoplasty between 2021 and 2023 with the new technique. Patients underwent a full clinical examination, consultation and facial analysis to examine the nose shape and identify any abnormalities and asymmetries in the face.In the study involving 50 patients, the majority41 (82%) werewere males, and most with (88%) had no history of prior rhinoplasty, primarily seeking aesthetic improvements in 44(88%) of participants. Facial asymmetry was observed in 35(70%) of the patients, with 42(84%) individuals exhibiting reduced nasal projection index, nasolabial angle, or nasofrontal angle. The novel technique achieved a straight nose outcome in 45(90%) of patients out of ,50, while 5(10%%) patients experienced mild deviation linked to extensive preoperative facial asymmetry.The surgery yielded highly satisfactory results in most patients, with straight nose outcomes being almost 10 times more likely than mild nose deviation outcomes, and no frank deviations. Throughout the follow-up period, none of the patients had complications, especially those that are common in other techniques attributed with extracorporeal septorhinoplasty, such as dorsal irregularities, septal perforation/deviation or abscesses.